Penerapan Arsitektur Futuristik pada Sirkuit Balap di Kabupaten Bulukumba - Resky, Ahmad Awal; Rahayu, Irma; Attar, Muhammad (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2024)
Futuristic architecture emerges from visionary ideas that embody freedom and forward-looking perspectives, manifesting in unconventional, creative, and innovative forms. Drawing upon literature and theoretical frameworks, this paper formulates several key principles of futuristic architecture: (1) integration of future-oriented concepts in building design; (2) adoption of unconventional and asymmetrical building shapes; and (3) utilization of cutting-edge technological advancements in structural design and construction practices. Employing a descriptive-qualitative analysis method, this study applies these principles through three case studies. Findings underscore that the juxtaposition of futuristic building forms against traditional environments accentuates their conceptualization of the future. Moreover, the degree of uniqueness and asymmetry directly influences the application of these principles, while advancements in structural technology reinforce their implementation.